Feasibility of an HIV self-testing intervention: a formative qualitative study among individuals, community leaders, and HIV testing experts in northern Tanzania - Bernard Njau; Esther Lisasi; Damian J. Damian; Declare L. Mushi; Andrew Boulle; Catherine Mathews (BMC, 2020)
Abstract Background Achieving the 95-95-95 global targets by 2030, innovative HIV testing models, such as HIV self-testing are needed for people, who are unaware of their HIV status. We aimed to explore key informants, mountain climbing porters, and female bar workers' attitudes, perceived norms, and personal agency related to HIV self-testing. Methods This was a formative qualitative study to inform the design of an HIV self-testing intervention in Northern Tanzania. Informed by the Integrated Behaviour Model, we conducted four focus group discussions, and 18 in-depth interviews with purposively selected participants. Data were analyzed using the framework method. Results We recruited 55 participants. Most participants had positive attitudes towards HIVST, in that they anticipated positive consequences related to the introduction and uptake of HIVST. These included privacy and convenience, avoidance of long queues at health facilities, reduced counselor workload, and reduced indirect costs (given that transport to health facilities might not be required). Participants expressed the belief that significant people in their social environment, such as parents and peers, would approve their uptake of HIVST, and that they would accept HIVST. Additionally, features of HIVST that might facilitate its uptake were that it could be performed in private and would obviate visits to health facilities. Most participants were confident in their capacity to use HIVST kits, while a few were less confident about self-testing while alone. Strategies to maximize beliefs about personal agency and facilitate uptake included supplying the self-test kits in a way that was easy to access, and advocacy. Perceived potential constraints to the uptake of HIVST were the cost of buying the self-test kits, poverty, illiteracy, poor eyesight, fear of knowing one's HIV status, lack of policy/ guidelines for HIVST, and the absence of strategies for linkage to HIV care, treatment, and support. Conclusions The findings suggest that HIVST may be feasible to implement in this study setting, with the majority of participants reporting positive attitudes, supportive perceived norms, and self-efficacy. Hence, future HIVST interventions should address the negative beliefs, and perceived barriers towards HIVST to increase HIV testing among the target population in Northern Tanzania.